1992
DOI: 10.1016/0921-5093(92)90314-q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of molybdenum disilicide by mechanical alloying

Abstract: This report was prepared as an account of work sponsorex:l by an agency of the Unite_ Statesany agency any ._I_ _eTE R Government. Neither the United States Government nor thereof, nor of their |_;; employees, makes any warranty, express or implied, or assumes any legal liability or responsi-|'._ _ _=_,_t bility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Refer-_': ___ ence here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(47 citation statements)
references
References 12 publications
4
43
0
Order By: Relevance
“…The high energy state of MM powder and formation of liquid phase due to melting of Si caused lower sintering temperature and shorter time to achieve near theoretical density in the VHP process. The similar observation has been noticed by Schwarz et al [12] for hot pressing of MoSi 2 powder made in high energy Spax mill. …”
Section: Isrn Metallurgysupporting
confidence: 72%
“…The high energy state of MM powder and formation of liquid phase due to melting of Si caused lower sintering temperature and shorter time to achieve near theoretical density in the VHP process. The similar observation has been noticed by Schwarz et al [12] for hot pressing of MoSi 2 powder made in high energy Spax mill. …”
Section: Isrn Metallurgysupporting
confidence: 72%
“…The reduction in the intensity of the Si peaks with milling is in agreement with previous observations. 6,7 It was suggested that the reduction is the consequence of the dissolution of Si in Mo or the formation of the silicide phase. The fact that in our study no such observation was made on Si powders milled separately would lend support for the proposed explanation.…”
Section: Fig 2 (A) Xrd Patterns Of Mo As a Function Of Charge Ratiomentioning
confidence: 99%
“…The value of B(g) was determined from the diffraction profile of a strain-free, wellannealed, coarse-grained specimen of LaB 6 . As suggested in the literature, 22 the variation of B(g) versus was obtained by fitting the measured breadth of the diffraction peaks of the standard material, using the following polynomial function:…”
Section: B( F ) ‫ס‬ B(h) − B(g)mentioning
confidence: 99%
See 2 more Smart Citations